Psychologicall Well-Being Mahasiswa Yang Mengalami Verbal Abuse di Program Studi Psikologi Kristen IAKN Manado - Sharon Kakambong; Astrid L. Mandas; Fienny M. Langi (Journal Of Psychology humanlight, 2024)
This research is motivated by psychological well-being of IAKN Manado students who have experienced verbal abuse, and the purpose of this study is to the descriptive of psychologicall well-being of students who experience verbal abuse. This research is a qualitative research with a descriptive approach carried out on students in the Christian Psychology Study Program of the Manado State Christian Institute. In collecting data from this research, researchers carry out several stages, namely observations, interviews and documentation, then researchers collect data by conducting interviews with informants with criteria that have experienced verbal abuse in dating relationships. From the results of this research, it can provide an overview of students who have experienced verbal abuse who have low psychological well-being. They show distrustful behavior in building new relationships, have a tendency to rely on the judgment of their couple who is still in a relationship, isolated from the social environment, have poor communication, feel self-lost, low self-esteem, and lack of self-awareness. But they can recover over time.